Improved Business Driveway Channelizing Treatments in Work Zones. Issue 1 (January 2015) - Theiss, LuAnn; Gillette, George F.; Ullman, Gerald L.
This paper documents the efforts and results of a human factors study of alternative business driveway channelizing treatments in work zones. The purpose of the research was to determine the effectiveness of alternative business driveway channelizing treatments over standard drum treatments. The alternative treatments included combinations of 18-in. low-profile longitudinal channelizing devices and 42-inch tall cones (i.e., grabber cones). Using paid participants who drove an instrumented vehicle, the researchers used driver eye-tracking equipment to compare differences in drivers' visual attention while approaching business driveways with the various channelization treatments deployed. Other measures of effectiveness considered were detection distance, percentage of missed driveways, driver perception and recall of treatments, and driver preferences. Although differences in the measures of effectiveness were less pronounced during the day, the alternative channelizing treatments generally performed better than the standard drum treatment at night.